2015
DOI: 10.1159/000440726
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Clinical Trial of Dialogical Exposure Therapy versus Cognitive Processing Therapy for Adult Outpatients Suffering from PTSD after Type I Trauma in Adulthood

Abstract: Background: Although there are effective treatments for posttraumatic stress disorder (PTSD), there is little research on treatments with non-cognitive-behavioural backgrounds, such as gestalt therapy. We tested an integrative gestalt-derived intervention, dialogical exposure therapy (DET), against an established cognitive-behavioural treatment (cognitive processing therapy, CPT) for possible differential effects in terms of symptomatic outcome and drop-out rates. Methods: We randomized 141 treatment-seeking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 37 publications
(39 reference statements)
0
20
1
Order By: Relevance
“…In order to explore this interaction further, the usual procedure would be to calculate and compare effect sizes. We did so, but the resultant subsample effect sizes were very inflated compared with those for the whole sample (Butollo, Karl, König, & Rosner, ), probably due to low variances in the subsamples. Therefore, we decided to present the data in the form of a figure only.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In order to explore this interaction further, the usual procedure would be to calculate and compare effect sizes. We did so, but the resultant subsample effect sizes were very inflated compared with those for the whole sample (Butollo, Karl, König, & Rosner, ), probably due to low variances in the subsamples. Therefore, we decided to present the data in the form of a figure only.…”
Section: Resultsmentioning
confidence: 97%
“…In this study, we report data collected for a study comparing the outcomes of two treatments for PTSD (Butollo et al , ). The study was performed at a university‐based outpatient clinic and was approved by the institution's ethics committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, memory impairment in mice may persist for extended periods beyond the presentation of predatory stress [8]. Besides, some studies have suggested that patients with PTSD develop impairments in working memory, delayed memory, instantaneous memory, attention, figural memory and visuospatial ability [9][10][11]. Furthermore, trauma survivors who express higher levels of early PTSD symptoms have impaired immediate figural memory and delayed figural memory, which indicates that they are more likely to develop full-blown PTSD in the future [12].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, FU data from humanistic approaches to PTSD therapy have not been published so far. We recently compared one such therapy, dialogical exposure therapy (DET) with CPT in a randomized trial including adults with PTSD (Butollo et al, 2016). DET is an integrative treatment with a foundation in gestalt therapy.…”
mentioning
confidence: 99%